PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH PLASTIK MENJADI ECOBRICK DALAM KERANGKA PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Masni; Zose Wirawan; Rizki Trisnawaty Arwien; Asriati, Asriati; Sukri Badaruddin; Asriadi, Muhammad (Media Inovasi Pendidikan dan Publikasi, 2025)
The high volume of plastic waste in Indonesia highlights the urgent need for community empowerment in managing waste creatively and sustainably. This community service program aims to raise awareness and enhance local skills through ecobrick production training in collaboration with the Utit Cokonuri Waste Bank group and its integration into the Strengthening the Pancasila Student Profile Project (P5). The implementation method adopted a participatory approach consisting of four main stages: needs assessment, technical planning, ecobrick training, and ongoing mentoring. The results show significant improvements in participants’ knowledge and technical skills in processing plastic waste into functional ecobricks. A total of 50 ecobrick units were successfully produced as pilot products and utilized as simple public facilities around the waste bank area. In addition, collaboration with partner schools facilitated the integration of ecobrick practice into P5 thematic projects on Sustainable Lifestyles, enabling students to actively participate in waste reduction practices. This success not only generated technical and environmental benefits but also opened economic opportunities through recycled products with added value. The program demonstrates the importance of synergy among universities, communities, and schools to support local sustainable development while strengthening Pancasila values through contextual learning. This empowerment model is expected to be replicated in other areas facing similar challenges to broaden its positive impact. The high volume of plastic waste in Indonesia highlights the urgent need for community empowerment in managing waste creatively and sustainably. This community service program aims to raise awareness and enhance local skills through ecobrick production training in collaboration with the Utit Cokonuri Waste Bank group and its integration into the Strengthening the Pancasila Student Profile Project (P5). The implementation method adopted a participatory approach consisting of four main stages: needs assessment, technical planning, ecobrick training, and ongoing mentoring. The results show significant improvements in participants’ knowledge and technical skills in processing plastic waste into functional ecobricks. A total of 50 ecobrick units were successfully produced as pilot products and utilized as simple public facilities around the waste bank area. In addition, collaboration with partner schools facilitated the integration of ecobrick practice into P5 thematic projects on Sustainable Lifestyles, enabling students to actively participate in waste reduction practices. This success not only generated technical and environmental benefits but also opened economic opportunities through recycled products with added value. The program demonstrates the importance of synergy among universities, communities, and schools to support local sustainable development while strengthening Pancasila values through contextual learning. This empowerment model is expected to be replicated in other areas facing similar challenges to broaden its positive impact